Establishing a Creative Innovation Framework for Informal Micro–Enterprises: Array - Mulibana, Lavhelesani; Rena, Ravinder (Acta Universitatis Danubius. Œconomica, 2021)
The existing innovation models assume an established innovation system and do not provide direct support on a practical level on what activities should be carried out in each basic innovation phase. The study sought to design a tailored creative innovation framework that can serve as a guide for informal micro-enterprises to engage in radical and incremental innovation. Through the application of sequential explanatory mixed-methods research, both quantitative and qualitative data were collected from 400 informal micro-enterprises in four townships of the Gauteng Province, South Africa. The data were analysed using descriptive statistics, correlation analysis, factor analysis, thematic, and constant comparison methods. The results reveal that informal micro-enterprises require guidance on how to engage in innovation activities throughout all basic innovation phases, which is from discovery to launch. Thus, there is a great deal of innovation-related support required in the informal sector. The study concludes that with proper guidance more informal micro-enterprises will engage in innovation activity and become sustainable. Sustainable informal micro-enterprises can create jobs and some of them will register to become formal businesses, thereby increasing the Government's tax base. A flourishing informal sector will aid in resolving South African and other developing countries' economic challenges.